Decolonising Disability: Quandamooka Weaving ... - Cooms, Samantha (CQUniversity, 2023)
This thesis explores the voice of Australia’s First Nation Quandamooka community of Moreton Bay, Queensland, in caring for one another, with a special focus on disability. First Nations peoples experience some of the poorest social, health and economic outcomes of any group in Australia and experience higher rates of disability than non-Indigenous Australians. Their experience of disability is compounded by institutional racism in the health care sector as well as the ongoing impact of colonisation. Whilst previous research has focused on vulnerabilities, there is little known of the strengths of First Nations communities in managing and negotiating disabilities, or the role of traditional knowledges and practices in this space and its contribution to sustainability and inclusion. This research project aims to capture and elevate the voices of the Quandamooka community with the intention of furthering the decolonisation of the disability sector. The project aims to add to the body of knowledge in a manner ...